Álvaro Lins: leitor de Graciliano Ramos - Rodrigues, Marcos Antonio [UNESP] (2015)
Álvaro Lins (1912-1970) through his critical-journalistic, developed a work that, in the first moment, was restricted more to the biography and psychology of writers. Later, he tries to break free of Impressionism content trend, adopting a scientific character for book review. Thus, we aim in this work approach it as reader of Graciliano Ramos (1892-1953); to this end, has been with analysis fulcrum three written tests on about fiction of Brazilian writer that are compiled in the afterword of Barren Lives (Values and Miseries of Barren Lives): I - Graciliano Ramos in terms of construction of the novel and style art; II - Memories of the novelist explain the nature and kind of his novels; III - Novels, novellas and short stories: vision block of a work of fiction writer. Thus intends to establish a brief outline of the thematic and formal procedures referred by Brazilian reviewer about the prose of the Brazilian novelist, and take into account that he was a pioneer in its reception, accompanied your route so that contributed to their consecration in our literature